Preliminary probiotic and technological characterization of Pediococcus pentosaceus strain KID7 and in vivo assessment of its cholesterol-lowering activity - Damodharan, Karthiyaini; Lee, Young Sil; Palaniyandi, Sasikumar A.; Yang, Seung Hwan; Suh, Joo-Won (Frontiers in Microbiology, 2015)
The study was aimed to characterize the probiotic properties of a Pediococcus pentosaceus strain, KID7, by in vitro and in vivo studies. The strain possessed tolerance to oro-gastrointestinal transit, adherence to the Caco-2 cell line, and antimicrobial activity. KID7 exhibited bile salt hydrolase activity and cholesterol-lowering activity, in vitro. In vivo cholesterol-lowering activity of KID7 was studied using atherogenic diet-fed hypercholesterolemic mice. The experimental animals (C57BL/6J mice) were divided into 4 groups viz., normal diet-fed group (NCD), atherogenic diet-fed group (HCD), atherogenic diet- and KID7-fed group (HCD-KID7), and atherogenic diet- and Lactobacillus acidophilus ATCC 43121-fed group (HCD-L.ac) as positive control. Serum total cholesterol (T-CHO) level was significantly decreased by 19.8% in the HCD-KID7 group (P<0.05), but not in the HCD-L.ac group compared with the HCD group. LDL cholesterol levels in both HCD-KID7 and HCD-L.ac groups were decreased by 35.5% and 38.7%, respectively, compared with HCD group (both, P<0.05). Glutamyl pyruvic transaminase (GPT) level was significantly lower in the HCD-KID7 and HCD-L.ac groups compared to HCD group and was equivalent to that of the NCD group. Liver T-CHO levels in the HCD-KID7 group were reduced significantly compared with the HCD group (P<0.05) but not in the HCD-L.ac group. Analysis of expression of genes associated with lipid metabolism in liver showed that low-density lipoprotein receptor (LDLR), cholesterol-7α-hydroxylase (CYP7A1) and apolipoprotein E (APOE) mRNA expression was significantly increase in the HCD-KID7 group compared to the HCD group. Furthermore, KID7 exhibited desired viability under freeze-drying and subsequent storage conditions with a combination of skim milk and galactomannan. P. pentosaceus KID7 could be a potential probiotic strain, which can be used to develop cholesterol-lowering functional food after appropriate human clinical trials.